Progress of selective catalytic reduction denitrification catalysts at wide temperature in carbon neutralization - Lin, Dehai; Zhang, Longhui; Liu, Zilin; Wang, Baodong; Han, Yifan (Frontiers in Chemistry, 2022)
With the looming goal of carbon neutrality and increasingly stringent environmental protection policies, gas purification in coal-fired power plants is becoming more and more intense. To achieve the NOx emission standard when coal-fired power plants are operating at full load, wide-temperature denitrification catalysts that can operate for a long time in the range of 260–420°C are worthy of study. This review focuses on the research progress and deactivation mechanism of selective catalytic reduction (SCR) denitration catalysts applied to a wide temperature range. With the increasing application of SCR catalysts, it also means that a large amount of spent catalysts is generated every year due to deactivation. Therefore, it is necessary to recycle the wide temperature SCR denitration catalyst. The challenges faced by wide-temperature SCR denitration catalysts are summarized by comparing their regeneration processes. Finally, its future development is prospected.